Systemological classification analysis in conceptual knowledge modeling - Данилов, А. Д.; Соловйова, К. О.; Бондаренко, М. Ф.; Слипченко, Н. И.; Бобровская, В. В. (ITHEA, 2010)
It is difficult to exaggerate the importance, the urgency and complexity of “good” classifications creation, especially in knowledge management, artificial intelligence, decision making. To what extend it is possible within a short paper, the peculiarities and advantages of the new system method of the systemological classification analysis for the classifications of concepts creation were discussed. It is noted that the systemological classification analysis on the basis of the natural classification improves considerably the quality and the power of the classification knowledge models and ontologies, allows taking into account the deep knowledge of any, including ill-structured, domains. In the process of the research conduction the system models of the domain fragment of the ontologies on the basis of the parametric classification were created. Some results of the actual domain “Social Networks in Internet” analysis and modelling and the ontology fragments, realized in the ontologies engineering tool Protégé 3.2, are also considered. The systemological classification analysis application has allowed proving the obtained classifications of social networks functions, taking into account the objects essential properties. It has also successfully recommended itself for deep knowledge acquisition; the basic hierarchy of classes, “good” classifications and ontologies creation; possesses predictive power, simple logically relevant structure, ensures the possibility of the correct inference on knowledge.
Keywords: conceptual knowledge; artificial intelligence; hierarchy; systemology; social network; systemological classification analysis; knowledge; natural classification; ontology; systemological classification analysis; knowledge systematization